Secondary Spontaneous Pneumothorax in Former Pulmonary Tuberculosis: a Case Report - Rijal, Syamsu; Aisyah, Windy Nurul; Natsir, Bulkis; Yasin, Julian Muhammad (Journal La Medihealtico, 2024)
A 36-year-old male presented to the hospital with a chief symptom of dyspnea that began one day before admission and increased during the night upon admission. The individual does not experience nausea, vomiting, heartburn, and has regular urination and normal bowel movements. Loss of appetite and fatigue. There is no prior record of comparable grievances. The existence of a history of trauma cannot be refuted. Past medical history: The patient had pulmonary TB and completed treatment in April 2023. During the physical examination, the patient's overall condition was observed to be moderately unwell, with a clear and alert state of consciousness. Assessment of vital signs revealed a blood pressure of 117/84 mmHg, a pulse rate of 65 beats per minute, a respiratory rate of 25 breaths per minute, a body temperature of 37°C, and an oxygen saturation level of 94%. In the thoracic region, the examination reveals the following findings: - Inspection shows movement of the chest wall on the left side. - Palpation detects weakened tactile fremitus on the left side. - Percussion produces a hypersonor sound on the left side. - Auscultation reveals normal vesicular sounds on the right side and weak vesicular sounds on the left side. Rhonchi are not present, but wheezing is heard in both sides of the chest. The supporting studies yielded a complete blood count within normal range, a VCT examination showing non-reactive HIV antibodies, a TCM sputum examination with undetectable MTB findings, and a chest X-ray examination indicating left pneumothorax and active pulmonary TB.